The 100 best vegan baking recipes : amazing cookies, cakes, muffins, pies, brownies and breads / Kris Holechek Peters - Holechek Peters, Kris
Contains one hundred simple recipes for vegan cookies, cakes, and pastries, including egg and dairy replacements and recipes for a variety of toppings.